Time-frequency connectedness between climate exchange-traded funds and climate policy uncertainty - Mohammad Enamul Hoque; Lain-Tze Tee; Md Akther Uddin; Si-Roei Kew; Faik Bilgili (Borsa Istanbul Review)
Global warming pressures legislators to alter climate policies to steer the world economy on a path with a net zero carbon footprint. This study examines the returns and volatility connectedness and the spillover of climate exchange-traded funds with climate policy uncertainty in the time-frequency domains. This research explores the influence of investors’ attention to climate change and uncertainty factors. The results reveal that climate policy uncertainty and exchange-traded funds share high returns and volatility connectedness across time, in which short-term connectivity dominates long-term connectivity. The results across the different frequencies indicate that climate attention, global carbon emission futures, oil market uncertainty, global economic policy, geopolitical risk, and global financial stress play an important role in the connectedness between climate policy uncertainty and climate exchange-traded funds. The empirical findings can help green investors choose the best exchange-traded funds depending on their investment horizon.